Physicochemical characterization of soiling from photovoltaic facilities in arid locations in the Atacama Desert. (15th July 2019) - Ferrada, Pablo; Olivares, Douglas; del Campo, Valeria; Marzo, Aitor; Araya, Francisco; Cabrera, Enrique; Llanos, Jaime; Correa-Puerta, Jonathan; Portillo, Carlos; Román Silva, Domingo; Trigo-Gonzalez, Mauricio; Alonso-Montesinos, Joaquín; et al.
Highlights: Ground and deposited dust on PV modules was analyzed for 4 sites in Atacama Desert. Deposited material is in the diameter range 1–60 µm, with peak frequency in 1–10 µm. A particle shape factor close to 1 had the largest frequency for all sites (40–70%). Dust from module surface and ground was analyzed by powder X-ray diffraction. The main components of dust were quarzt, albite, anorthite and orthoclase. Abstract: Soiling is an issue that impacts the performance of photovoltaic (PV) technologies as it attenuates the amount of solar resource reaching the solar cells. The chemical composition of the soil is essential to define cleaning strategies of photovoltaic companies. This paper reports the characterization of the chemical and physical properties of the soiling deposited on photovoltaic modules located in the Atacama Desert. The particle size, shape and chemical composition of dust were studied at 4 different locations (denoted as L1 to L4) with samples taken from the ground and the module surface. It was found that, most deposited material exhibits a diameter between 1 µm and 60 µm. The determination of the particle shape factor shows that smaller particles tend to have a circular appearance, while larger particles exhibit a prismatic form. These small particles show a shape factor close to 1 and occur at the 4 locations with the greatest frequency, 40–70%. The mineral species in both the deposited and ground dust, which were identified by means of X-ray diffraction, were albite, anorthite, calcite, cristobalite, gypsum, halite, quartz, muscovite and orthoclase. The compounds occurring with the highest frequency in both the module and ground dust at all locations were quartz and anorthite. Differences between the locations were found. Calcite was found only at L3. Gypsum was not detected at L1 and L3 but was present in L2 and L4. Similarly, cristobalite was found only at L1 and L3, halite was found at L2 and L3, and muscovite was found at L1 and L2.